Contribution of rice fields to bird diversity in Peninsular Malaysia - Nur Munira Azman; Shahrul Anuar Mohd Sah; Amirrudin Ahmad; Nik Fadzly N Rosely (Penerbit Universiti Kebangsaan Malaysia, 2019)
There is a lack of documentation on rice fields as an important habitat that harbour different bird diversity compared to natural habitats in Peninsular Malaysia. This study investigated the contribution of rice fields to bird diversity in Peninsular Malaysia. A total of 83 rice fields and 53 natural habitats throughout Peninsular Malaysia were included in this study. Birds were observed and counted using point-count and mist-netting methods. A total of 10,707 bird-sightings, with rice fields, recorded 129 species from 15 orders and 50 families from October 2013 to December 2014; whilst natural forests recorded a total of 438 species from 14 order and 59 families from February 1992 to January 2015. Diversity t-test showed a significant difference in the species richness between the two different habitats (t=11.009, p<0.05). The high values of Δ+and ʌ+ in many areas of rice fields were significantly influenced by the presence of waterbirds, albeit low species richness. This temporary wetland habitat harbours land birds and waterbirds in one place. The data presented here suggest that waterbirds and migratory birds in rice fields contribute significantly to the total bird species found in Peninsular Malaysia.